Аналіз методів захисту інформації, що знаходять використання у сучасних месенджерах - Білокуров, О. О.; Майба, М. А.; Шлома, О. К.; Дробяз, М. О. (ХНУРЕ, 2022)
Currently, mobile technologies have become an integral part of everyday life. With their development, specialized instant messaging services have become available, gradually replacing standard short text messaging services. Unlike simple SMS, messengers use the public Internet. Most users choose messenger for simplicity and ease of use. In addition, as often happens, users think less about security issues. In general, they do not mention this at all when choosing and using messengers. Therefore, the paper analyzes the information protection methods used in modern messengers.
Keywords: захист інформації; Signal; шифрування; месенджер